2018
DOI: 10.1016/j.carbon.2017.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Active modulation of electromagnetically induced transparency analogue in terahertz hybrid metal-graphene metamaterials

Abstract: Metamaterial analogues of electromagnetically induced transparency (EIT) have been intensively studied and widely employed for slow light and enhanced nonlinear effects. In particular, the active modulation of the EIT analogue and well-controlled group delay in metamaterials have shown great prospects in optical communication networks. Previous studies have focused on the optical control of the EIT analogue by integrating the photoactive materials into the unit cell, however, the response time is limited by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
168
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(170 citation statements)
references
References 105 publications
2
168
0
Order By: Relevance
“…In the lower THz range, the interband contributions can be completely ignored. Because of Pauli exclusion principle, the surface conductivity can be approximated as a Drude-like model [41,42].…”
Section: The Geometric Structure and Numerical Modelmentioning
confidence: 99%
“…In the lower THz range, the interband contributions can be completely ignored. Because of Pauli exclusion principle, the surface conductivity can be approximated as a Drude-like model [41,42].…”
Section: The Geometric Structure and Numerical Modelmentioning
confidence: 99%
“…Recent studies have shown that the EIT effect can be mimicked by a series of classical optical systems, such as on-chip plasmonic structures [2], photonic crystals [3][4][5] and meta-surfaces [6][7][8][9][10]. Apart from its fundamental significance, meta-surface-induced transparency in subwavelength structures is the most recent and promising addition to the existing classical EIT schemes [11][12][13]. Terahertz bandpass devices, such as the THz modulators and sensing devices [14], have been developed by applying the transparency window of the EIT.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al observed the excitation and tuning of EIT by the interference between different excitation pathways of the dark mode in a planar terahertz metamaterial [10]. Xiao et al realize a complete modulation in the resonance strength of the EIT analog via manipulating the conductivity of graphene [11].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional EIT, which requires severe experimental conditions [18], MM-based EIT analogue is easier to be produced and more stable, therefore suitable for practical chipscale applications [15].At the same time, for THz communication systems, THz devices with active tunability are required [19]. Therefore, various active optical materials have been utilized to turn passive MMs to be active, including liquid crystals [20,21], semiconductors [19,22,23], two-dimension (2D) materials [24][25][26] and phase-change materials (PCMs) [27]. PCMs, such as chalcogenide GeSbTe (GST) and vanadium dioxide (VO2), possess significantly different optical properties in different phase states, i.e., amorphous and crystalline states [28].…”
mentioning
confidence: 99%